Case Report: Novel STIM1 Gain-of-Function Mutation in a Patient With TAM/STRMK and Immunological Involvement - de la Fuente-Munoz, Eduardo; Van Den Rym, Ana; García-Solis, Blanca; Ochoa Grullón, Juliana; Guevara-Hoyer, Kissy; Fernández-Arquero, Miguel; Galán Dávila, Lucía; Matías-Guiú, Jorge; Sánchez-Ramón, Silvia; Pérez de Diego, Rebeca (Frontiers in Immunology, 2022)
Gain-of-function (GOF) mutations in STIM1 are responsible for tubular aggregate myopathy and Stormorken syndrome (TAM/STRMK), a clinically overlapping multisystemic disease characterised by muscle weakness, miosis, thrombocytopaenia, hyposplenism, ichthyosis, dyslexia, and short stature. Several mutations have been reported as responsible for the disease. Herein, we describe a patient with TAM/STRMK due to a novel L303P STIM1 mutation, who not only presented clinical manifestations characteristic of TAM/STRMK but also manifested immunological involvement with respiratory infections since childhood, with chronic cough and chronic bronchiectasis. Despite the seemingly normal main immunological parameters, immune cells revealed GOF in calcium signalling compared with healthy donors. The calcium flux dysregulation in the immune cells could be responsible for our patient’s immune involvement. The patient’s mother carried the mutation but did not exhibit TAM/STRMK, manifesting an incomplete penetrance of the mutation. More cases and evidence are necessary to clarify the dual role of STIM1 in immune system dysregulation and myopathy.